Currencies and crises - Krugman, Paul R (London, 1995)
Paul Krugman's first collection of essays, Rethinking International Trade, mounted a spirited assault on established trade theory and proposed an alternative approach to account for increasing returns and imperfect competition. Less theoretical and more embedded in real-world experience, this new collection revolves around Krugman's work on international monetary economics from the late 1970s to the present in an effort to make sense of a turbulent period that "involved one surprise after another, most of them unpleasant." The eleven essays cover such key areas as the role of exchange rates in balance-of-payments adjustment policy, the role of speculation in the functioning of exchange rate regimes, Third World debt, and the construction of an international monetary system. They are unified by the same basic methodology and style the construction of a small theoretical model in order to simplify or clarify a puzzling or difficult world monetary problem.
Keywords: International finance